Method for improving voltage sag tolerance of dual power supply PET based on inter-port power coordination - ZHANG Tengfei; WANG Guanghua; GAO Long; LI Jing; XU Yonghai; WANG Chong (电力工程技术)
Dual power supply cascaded-type power electronic transformers (DPSC-PET) is connected to two power supplies with high operational reliability and flexible operation mode, and it can be widely used in medium and low voltage distribution networks. It is of great importance to conduct in-depth research on its voltage sag tolerance and regulation method for maintaining efficient energy transmission of DPSC-PET as well as high quality power supply during voltage sag. Firstly, the topological structure and control strategy of DPSC-PET are analyzed. Secondly, the influence factors of voltage sag tolerance of DPSC-PET are analyzed for three-phase symmetrical voltage sag which has the most serious power shortage. Then, from the perspective of power balance, a real-time analysis method of voltage sag immunity of DPSC-PET as well as power coordination method between dual input ports when voltage sag occurs on different power supply are proposed to achieve a perfect recovery of low-voltage DC bus voltage, which means the significant improvement of DPSC-PET to cope with transient disturbances. Finally, the simulation model of DPSC-PET is established and the simulations for voltage sag occurred with different magnitudes on different power supply are cited out. The results show that the voltage sag tolerance of DPSC-PET is significantly improved with the proposed method.